Expressive Speech Acts of Politeness in The Counselling Process - Tri Budiarta; Joko Nurkamto; Sumarlam Sumarlam; Dwi Purnanto (Institut Agama Islam Negeri (IAIN) Kendari, 2021)
This study discusses the expressive speech acts of politeness in the counseling process. The study attempts to 1) identify the sub-types of expressive speech acts and their functions in the counseling process and (2) explain the realization of expressive speech act of politeness strategies in the counseling process. Data for the study were collected using passive participation observation and recording with closed-circuit television (CCTV). Data in this study were analyzed following the goal, heuristic method, and contextual methods. The findings of this study are associated with the stages of the counseling process. First, Building Relationships consists of sub-speech acts; Second, the Problem Identification Stage consists of sub-speech acts; Third, Facilitating Therapeutic Change consists of sub-actions speech act. Based on the findings of the study, praising is the most dominant utterance that always appears in every stage of the counseling process. It shows that the communication that happened in the counseling process is in a close, familial, warm, and comfortable atmosphere. This study demonstrates that language plays a critical role in the process of resolving human problems.